2022
DOI: 10.1002/mawe.202200019
|View full text |Cite
|
Sign up to set email alerts
|

Evolution mechanism of compression deformation of carbon black reinforced epoxy resin composites

Abstract: In this paper, the double-element composites were developed, which contained the epoxy resin as matrix phase and carbon black rubber powder as toughening materials. Quasi-static compression tests on epoxy resin and different mass fractions carbon black rubber powder-epoxy resin composites were performed in room temperature to test their compression properties. The energy absorption performance and the energy absorption efficiency of the composites were calculated according to the compression curve. The fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Lignin fiber/epoxy resin composites were prepared by atmospheric pressure stirring casting. The preparation of lignin fiber / epoxy resin composites includes surface treatment of lignin fiber, dilution of epoxy resin matrix material, stirring and curing of composites, etc [17,18]. E51 bisphenol A epoxy resin (guangzhou Suixin Chemical Co., LTD.) was selected as the matrix of the composite.…”
Section: Methodsmentioning
confidence: 99%
“…Lignin fiber/epoxy resin composites were prepared by atmospheric pressure stirring casting. The preparation of lignin fiber / epoxy resin composites includes surface treatment of lignin fiber, dilution of epoxy resin matrix material, stirring and curing of composites, etc [17,18]. E51 bisphenol A epoxy resin (guangzhou Suixin Chemical Co., LTD.) was selected as the matrix of the composite.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the previous research of our group, it was shown that carbon black rubber powder epoxy resin composites with a mass fraction of 5% showed the best mechanical properties [33], so in this study, fly ash hollow beads were used to toughen the rubber powder epoxy resin matrix with a mass fraction of 5%. Quasi-static compression tests were carried out using a universal testing machine to obtain stressstrain curves, focusing on the compression characteristics of the specimens.…”
Section: Introductionmentioning
confidence: 99%